2008
DOI: 10.1136/bmj.a716
|View full text |Cite
|
Sign up to set email alerts
|

Clomifene citrate or unstimulated intrauterine insemination compared with expectant management for unexplained infertility: pragmatic randomised controlled trial

Abstract: Objective To compare the effectiveness of clomifene citrate and unstimulated intrauterine insemination with expectant management for the treatment of unexplained infertility. Design Three arm parallel group, pragmatic randomised controlled trial. Setting Four teaching hospitals and a district general hospital in Scotland. Participants Couples with infertility for over two years, confirmed ovulation, patent fallopian tubes, and motile sperm. Intervention Expectant management, oral clomifene citrate, and unstimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
110
0
7

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(117 citation statements)
references
References 18 publications
(19 reference statements)
0
110
0
7
Order By: Relevance
“…In secondary infertility, it was observed that clinical pregnancy rates were 1.84-fold higher than in primary infertility. There are many studies in the literature supporting this data (20)(21)(22). However, contradictory conclusions have also been reported.…”
Section: Discussionmentioning
confidence: 77%
“…In secondary infertility, it was observed that clinical pregnancy rates were 1.84-fold higher than in primary infertility. There are many studies in the literature supporting this data (20)(21)(22). However, contradictory conclusions have also been reported.…”
Section: Discussionmentioning
confidence: 77%
“…In 1998 Guzick et al performed a retrospective review of the literature of women receiving clomiphene citrate +/− intrauterine insemination (IUI), and found the pregnancy rate was 6-8 % per cycle, compared to 2-4 % when not treated [26]. On the contrary, a recent large prospective study which randomised 600 women with unexplained infertility to clomiphene citrate, IUI or expectant management showed comparable results for all three arms in terms of delivery rates [27]. However, the mean age of participants in these studies was 31-32 years and results of clomiphene citrate involving delivery rates for women aged 40 and above are rarely reported and are seldom prospective studies.…”
Section: Ovulation Induction With Clomiphene Citrate and Intrauterinementioning
confidence: 99%
“…Observation data suggest three fold increases in pregnancy rates with IUI alone, with further increase in concomitant ovarian stimulation. (Bhattacharya et al, 2008).…”
Section: Discussionmentioning
confidence: 99%